2015
DOI: 10.3109/08990220.2015.1054025
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of plantar stimulation on human balance control

Abstract: The results showed that, differently from the firm and foam, the textured surface is able to increase the plantar feedback to maintaining postural control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Then the comparison between different reports appears non-standardized [52]. Among the several alternative methods for measuring ankle dorsiflexion, we have chosen the weight-bearing dorsiflexion since it better reflects the change of position characterizing physical activity [53]. In the present study, we have demonstrated that the training program characterized by proprioceptive exercise is able to significantly improve the dorsiflexion range of motion as compared to the control group.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Then the comparison between different reports appears non-standardized [52]. Among the several alternative methods for measuring ankle dorsiflexion, we have chosen the weight-bearing dorsiflexion since it better reflects the change of position characterizing physical activity [53]. In the present study, we have demonstrated that the training program characterized by proprioceptive exercise is able to significantly improve the dorsiflexion range of motion as compared to the control group.…”
Section: Discussionmentioning
confidence: 81%
“…In this study, the experimental group after a combined warm-up routine group showed a significant decrease in pathway length while the global warm-up routine control group decreased significantly the balance control confirmed also by a significant increase in the ellipse area. According to others studies [52,53] that upright posture tested in barefoot condition on a firm surface is able to reduce the body sway path compared with foam surface as represented by standard sports shoes. In fact, the balance barefoot exercise associated with core stability routine, which performed in experimental intervention significant decreases in body sway path (CoP displacement) compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PD patients that display severe gait impairments can particularly benefit from interventions based on mechanical stimulation of the plantar foot, thereby improving gait parameters and in turn limiting the adverse outcomes related to that impairment. Different methods of mechanical plantar foot sensory stimulation have been studied, including insoles with a raised ridge located at the foot's perimeter, mechanical pressure on the sole of the foot, and vibratory insoles [83]. Several studies have tested automated mechanical peripheral stimulation (patented as Gondola TM ) to facilitate the stimulation procedure through an electric motor that activates metallic stimulators with a diameter of 2 mm.…”
Section: Discussionmentioning
confidence: 99%
“…These reflect the function of health in the BDJ movement. The GT and 1st MTH sensation inputs from the skin contribute to the adjustments needed to maintain the body part of unstable, in order to keep the body upright when other parts are moving (Annino et al, 2015). It is anticipated that the make out of the characteristics of BDJ exercise has a positive clinical relevance for people who have problems keeping balance.…”
Section: Center Of Pressurementioning
confidence: 99%